Hypervalent Iodine-Mediated Beckmann Rearrangement of Ketoximes - Oishi, Ryohei; Segi, Kazutoshi; Hamamoto, Hiromi; Nakamura, Akira; Maegawa, Tomohiro; Miki, Yasuyoshi (Synlett, 2018)
We developed a Beckmann rearrangement employing hypervalent iodine reagent under mild conditions. The reaction of ketoxime with hypervalent iodine afforded the corresponding ketone, but premixing of hypervalent iodine and a Lewis acid was effective for promoting Beckmann rearrangement. Aromatic and aliphatic ketoximes were converted into their corresponding amides in good to high yields.
Keywords: hypervalent iodine reagent; Beckmann rearrangement; oxime; amide; Lewis acid